2011
DOI: 10.1089/met.2011.0016
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzymes, Type 2 Diabetes, and Metabolic Syndrome in Middle-Aged, Urban Chinese Men

Abstract: In this representative sample of middle-aged Chinese men, elevated ALT and AST were associated with a prevalence of metabolic syndrome and T2D. These findings suggest that the relationship between obesity and T2D might involve liver injury. Physical activity might reduce the levels of ALT and AST, probably mediated through weight reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
5
22
0
Order By: Relevance
“…Finally, several reports indicate the existence of an association between elevated serum levels of liver enzymes and T2D [42,43]. According to previous data reporting beneficial effects of olive oil consumption on fatty liver [44,45], the decreased levels of AST and ALT, indirect circulating markers of liver injury, seem to be a further positive response to the HP-EVOO consumption in our subjects.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, several reports indicate the existence of an association between elevated serum levels of liver enzymes and T2D [42,43]. According to previous data reporting beneficial effects of olive oil consumption on fatty liver [44,45], the decreased levels of AST and ALT, indirect circulating markers of liver injury, seem to be a further positive response to the HP-EVOO consumption in our subjects.…”
Section: Discussionsupporting
confidence: 68%
“…They predicted the involvement of liver injury associated with obesity and type II diabetes. 31 Similar observations were also concluded from a study conducted in Thailand among Thai adults.…”
Section: Discussionsupporting
confidence: 79%
“…MS, defined as a constellation of interrelated metabolic abnormalities, is prevalent in China. MS prevalence has been reported to be from 6.6% to 25.6% in the Chinese population891516, while the latest report showed that this figure jumped to 33.9%3. The key mechanisms of MS were related with insulin resistance, obesity, chronic low-grade systemic inflammation, endothelial dysfunction, etc.…”
Section: Discussionmentioning
confidence: 99%